POJOK BACA LASKAR CENDIKIA: INOVASI LITERASI MASYARAKAT DESA BERIRIJARAK - Ermiana, Ida; Amin, Fitrah Maulidi; Bimandry, Muhammad Alif; Syafira, Lale Rahma; Niza Yunita; Fauzi, Asri; Rahmatih, Aisa Nikmah (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
Literacy is a person's ability and skill in processing and understanding information from writing and reading activities. Reading plays an important role in the learning process as a means to absorb knowledge or understand a text. Reading as a cognitive process that seeks to find information in the text. The reading interest and reading ability of students is currently worrying, due to less interesting learning methods and public perceptions that prioritize basic needs such as food and clothing. Beririjarak Village, in East Lombok Regency, faces similar challenges, where early childhood is often involved in agricultural work and limited access to early literacy such as reading and writing before entering school. The objectives of establishing a reading corner include: increasing literacy, especially students' interest in reading. The implementation methods used are observation, interviews and collaboration with the village, as well as conducting socialization to the community and early childhood. The results of the program implementation show an increase in literacy, especially the interest in reading and participation of early childhood in literacy activities. The Reading Corner Program is a significant step in increasing early childhood literacy and providing them with access to learn to read, write, and count outside the school context. Through a comprehensive approach, including socialization and direct practice with early childhood, the Reading Corner program has succeeded in increasing their participation in literacy activities